Early- and Late-Respiratory Outcome in Very Low Birth Weight with or without Intrauterine Inflammation - Perniciaro, Simona; Casarin, Jvan; Nosetti, Luana; Binda, Chiara; Salvatore, Silvia; Ghezzi, Fabio; Agosti, Massimo (American Journal of Perinatology, 2020)
• IUI is a risk factor for spontaneous preterm birth and contributes to prematurity-associated mortality and morbidity.• HCA greatly affected Apgar’s score and lung management of VLBWI at birth and later on with increased incidence of BPD.• HCA + FUN did not significantly impact on respiratory outcome.Objective Intrauterine inflammation or infection (IUI) is a risk factor for spontaneous preterm birth and contributes to prematurity-associated mortality and morbidity. IUI can include inflammation, as well as infections of varying degrees of severity and duration. Histological chorioamnionitis (HCA) remains the “gold standard” for the diagnosis but clinical, microbiological, and biochemical criteria are often used to define chorioamnionitis. The impact of intrauterine inflammation on respiratory outcome, in infants with very low birth weight, is still unclear and previous data are conflicting showing increase, decrease, or no risk of respiratory complications.Study Design This is a retrospective study aimed to investigate the role of IUI on neonatal respiratory outcome. Histological criteria (HCA alone and HCA + funisitis [FUN]) and “intrauterine inflammation or infection or both” “Triple I” definition were used; different management in delivery room, in the first 7 days of life (early outcome) and incidence of mild, moderate, and severe bronchopulmonary dysplasia (BPD; late outcome) were considered.Results A total of 162 infants with very low birth weight (VLBW) with placenta histology were enrolled. Suspected TRIPLE or fever alone was present in 7.4%, and confirmed TRIPLE or HCA in 29.6% of cases (HCA alone 19.1% vs. HCA + FUN 10.5%). Preterm premature rupture of membrane (p-PROM) was strongly associated with HCA (66.6% in HCA group) and HCA was present in 80% neonates born between 22 and 24 weeks of gestational age (GA). HCA group (GA, 26 weeks; birth weight [BW], 880 g) showed lower Apgar's score, higher intubation rate, and need of ventilation in delivery room, surfactant, duration of noninvasive ventilation (NIV), severe patent ductus arteriosus (PDA), and incidence of BPD compared with no-HCA (GA, 30 weeks; BW, 1,210 g). Length of hospital stay and mortality were higher in HCA group (p = 0.01) and an increasing trend was present for HCA + FUN compared with HCA alone.Conclusion HCA greatly affected Apgar's score and lung management of VLBW infants (VLBWI) at birth and later on with increased incidence of BPD, thus impacting length of stay and quality of life, while HCA + FUN did not significantly impact on respiratory outcome. Further studies are needed to clarify the role of HCA and FUN in VLBW neonates.
Keywords: very low birth weight; histological chorioamnionitis; histological funisitis